Panda Panic Running wild - Rix, Jamie (Awesome animals, 2012)
Sit around eating bamboo all day? No way! Ping wants to have wild adventures so when he hears that one lucky panda will get a chance to travel the world, he can hardly contain his excitement. But how to make sure it's him that's chosen?